The group of paintings "Oświęcim/Auschwitz" (1947–1955) by Xawery Dunikowski – the artistic testimony of borderline experience - Tomczak, Karolina (Papers in Literature, 2023)
This article presents an analysis of Xawery Dunikowski’s post-war paintings, a testimony to his stay in the Auschwitz concentration camp, i.e. the canvases of the cycle Oświęcim/Auschwitz (1947–1955). Based on this infrequently discussed kind of art, an attempt has been made to describe the visual representation of borderline experience, which, according to Georges Didi-Huberman, is a “tear-image” or a glimpse of an incomprehensible unprecedented truth, urging to a particularly cruel imaginability or, as Luiza Nader puts it, an expression of “affective memory”. At the same time, the considerations contribute to the research discourse on whether or to what extent it is possible to express the experience of a Konzentrationslager (or, more broadly, the Second World War) in visual representation. The complex issues and stylistics of these works are discussed in the light of methodology concerning the trauma of a witness, an affective observer, a surviving victim (Jacek Leociak, Aleida Assmann, Dominick LaCapra) and its evocation in the image (Didi-Huberman, Nader) thus allowing to consider them as a necessary artistic catharsis of the author of Tchnienie/A Breath of Air. At the same time, it has been pointed out that the painting of Dunikowski, a sculptor, individually reformulated in the artistic medium, non-masterly and in search of their own expression, is a recontextualising confirmation of his status as a modernist artist.